Catalyst for improving selectivity of phenoxylation to dicyclohexyl dicarboxylate, preparation method of catalyst and method for preparing dicyclohexyl dicarboxylate by phenoxylation
Patent Information
- Application Number
- CN202510572158.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0014](1)采用弱酸性分子筛材料及弱碱性氧化物复配,容易控制载体的酸碱性,对于提升产物的选择性有较大帮助。
Smart Images

Figure BDA0005388005900000191
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalysts, specifically relating to a catalyst for improving the selectivity of benzene oxidation to maleic anhydride, a method for preparing the catalyst, and a method for benzene oxidation to maleic anhydride. Background Technology
[0002] Maleic anhydride (maleic anhydride) is an important organic chemical raw material that can be used to produce fine chemicals such as 1,4-butanediol, tetrahydrofuran, succinic acid, γ-butyrolactone, fumaric acid, and unsaturated polyester resins. It can also be used in the production of pharmaceuticals and pesticides.
[0003] Maleic anhydride can be produced from benzene through a partial oxidation reaction. This reaction is highly exothermic; if the heat generated during the reaction cannot be removed in time, local overheating will occur, causing benzene and maleic anhydride to burn violently at high temperatures, producing large amounts of carbon monoxide and carbon dioxide. Therefore, timely removal of the heat generated during the reaction is crucial for the partial oxidation of benzene. By improving catalyst selectivity, the amount of carbon monoxide and carbon dioxide produced can be reduced, essentially minimizing the heat of reaction. V-Mo catalysts play a very important role in the conversion of benzene to maleic anhydride. The main preparation process involves spraying active components containing V, Mo, and additives onto a catalyst support, followed by activation to prepare the catalyst. Silicon carbide is commonly used as the support, supplemented with a small amount of binder. In this preparation process, the support plays two main roles: firstly, it provides support for the active components; secondly, it removes the heat generated during the reaction in a timely manner, avoiding the formation of hot spots and reducing the generation of byproducts. Therefore, a high-performance support plays a vital role in improving the performance of the catalyst. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and provide a catalyst for improving the selectivity of benzene oxidation to maleic anhydride and its preparation method. By compounding weakly acidic molecular sieve materials and weakly basic oxides, a silicon carbide-weakly acidic-weakly basic ternary composite support is constructed. The selectivity of the catalyst for benzene oxidation to maleic anhydride is improved by utilizing the interaction between the support and the active components.
[0005] To achieve the above objectives, a first aspect of the present invention provides a catalyst for improving the selectivity of benzene oxidation to maleic anhydride, comprising a support and an active component supported on the support, wherein the support is a ternary composite support of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide.
[0006] Specifically, based on the total weight of the carrier, the content of the weakly acidic molecular sieve material is 0.1-10 wt%, preferably 1-5 wt%, and the content of the weakly basic oxide is 0.1-10 wt%, preferably 1-5 wt%.
[0007] A second aspect of the present invention provides a method for preparing the catalyst for improving the selectivity of benzene oxidation to maleic anhydride, comprising the following steps:
[0008] Step 1: Take silicon carbide, weakly acidic molecular sieve material and alkaline oxide, crush them, mix them with binder and solvent, extrude them into shape, and then dry and calcine them to obtain the carrier.
[0009] Step 2: Add the active substance to the reducing agent solution to obtain the active mother liquor;
[0010] Step 3: Spray the active mother liquor onto the carrier to obtain the catalyst precursor;
[0011] Step 4: Activate the catalyst precursor to obtain the catalyst for the oxidation of benzene to maleic anhydride.
[0012] A third aspect of the present invention provides a method for the oxidation of benzene to maleic anhydride, wherein a benzene-containing gas mixture is contacted with the catalyst described above for improving the selectivity of the oxidation of benzene to maleic anhydride.
[0013] The beneficial effects of this invention are:
[0014] (1) The use of weakly acidic molecular sieve materials and weakly basic oxides makes it easy to control the acidity and alkalinity of the carrier, which greatly helps to improve the selectivity of the product.
[0015] (2) Using the ternary composite carrier of the present invention, the existing active components are compounded to further improve the maleic anhydride yield.
[0016] (3) The carrier prepared by the present invention has a simple process, no major changes compared with the existing process, and the raw materials are readily available and the cost is low.
[0017] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation
[0018] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0019] To achieve the above objectives, a first aspect of the present invention provides a catalyst for improving the selectivity of benzene oxidation to maleic anhydride, comprising a support and an active component supported on the support, wherein the support is a ternary composite support of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide.
[0020] The weakly acidic molecular sieve material has a content of 0.1-10 wt%, preferably 1-5 wt%, based on the total weight of the carrier, and the weakly basic oxide has a content of 0.1-10 wt%, preferably 1-5 wt%, with the balance being silicon carbide.
[0021] According to the present invention, preferably, the weakly acidic molecular sieve material is selected from at least one of MCM-41 molecular sieve, MCM-48 and SBA-15, preferably MCM-41 molecular sieve, and preferably, the MCM-41 molecular sieve has a silica-alumina ratio of 5-50 and a pore size of 2-8 nm.
[0022] In this invention, the molecular sieve was purchased from Innoca.
[0023] According to the present invention, preferably, the weakly basic oxide is selected from at least one of CeO2, MgO, ZnO and Ag2O.
[0024] According to the present invention, preferably, the ternary composite carrier of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide is obtained by mixing, extruding, drying and calcining silicon carbide, weakly acidic molecular sieve material, weakly basic oxide, binder and solvent.
[0025] According to the present invention, preferably, the ternary composite carrier of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide is at least one of spherical, cylindrical, annular, clover-shaped and tetraclover-shaped.
[0026] According to the present invention, preferably, the adhesive is selected from at least one of methylcellulose, polypropylene, starch, and dextrin.
[0027] According to the present invention, preferably, the solvent is water and / or ethanol.
[0028] According to the present invention, preferably, the loading of the active component is 10-30 wt%, more preferably 12-24 wt%, based on the total weight of the catalyst.
[0029] According to the present invention, preferably, the active component includes a main catalyst component and a co-catalyst component.
[0030] Preferably, the main catalyst component includes vanadium, molybdenum, sodium, phosphorus, and nickel.
[0031] Preferably, the co-catalyst component includes alkali metal and / or transition metal elements, and is preferably selected from two elements selected from cesium, potassium, titanium, niobium, silver, and copper.
[0032] According to the present invention, preferably, the molar ratio of vanadium, molybdenum, sodium, phosphorus, nickel and the co-catalyst component (calculated as metal elements) is 1:(0.2-0.90):(0.001-0.2):(0.005-0.25):(0.0001-0.05):(0.0002-0.010), wherein the molar amounts are respectively calculated as V2O5, MoO3, Na2O, P2O5 and NiO.
[0033] A second aspect of the present invention provides a method for preparing the catalyst for improving the selectivity of benzene oxidation to maleic anhydride, comprising the following steps:
[0034] Step 1: Take silicon carbide, weakly acidic molecular sieve material and alkaline oxide, crush them, mix them with binder and solvent, extrude them into shape, and then dry and calcine them to obtain the carrier.
[0035] Step 2: Add the active substance to the reducing agent solution to obtain the active mother liquor;
[0036] Step 3: Spray the active mother liquor onto the carrier to obtain the catalyst precursor;
[0037] Step 4: Activate the catalyst precursor to obtain the catalyst for the oxidation of benzene to maleic anhydride.
[0038] According to the present invention, preferably, in step 1, the drying conditions include: a temperature of 100-140°C and a time of 8-20h; the calcination conditions include: a temperature of 800-1200°C and a time of 2-10h.
[0039] According to the present invention, preferably, in step 2, the reducing agent is selected from at least one of oxalic acid, ammonium oxalate and urea.
[0040] According to the present invention, preferably, the compound containing the active substance includes a compound containing a main catalyst component and a compound containing a co-catalyst component.
[0041] Preferably, the compound containing the main catalyst component includes vanadium compounds, molybdenum compounds, sodium compounds, phosphorus compounds, and nickel compounds; the vanadium compound is preferably selected from at least one of ammonium metavanadate, vanadium pentoxide, and sodium vanadate; the molybdenum compound is preferably selected from at least one of ammonium molybdate, molybdenum trioxide, and calcium molybdate; the sodium compound is preferably selected from sodium dihydrogen phosphate and / or trisodium phosphate; the phosphorus compound is selected from at least one of ammonium dihydrogen phosphate, 85%-115% phosphoric acid, and phosphorus pentoxide; and the nickel compound is selected from at least one of nickel nitrate, nickel sulfate, nickel chloride, and nickel oxide.
[0042] Preferably, the compound containing the co-catalyst component includes alkali metal and / or transition metal compounds, and is preferably selected from two compounds of cesium, potassium, titanium, niobium, silver, and copper.
[0043] Preferably, the molar ratio of the vanadium compound (calculated as V2O5), the molybdenum compound (calculated as MoO3), the sodium compound (calculated as Na2O), the phosphorus compound (calculated as P2O5), the nickel compound (calculated as NiO), and the compound containing the co-catalyst component (calculated as metal element) is 1:(0.2-0.90):(0.001-0.2):(0.005-0.25):(0.0001-0.05):(0.0002-0.010).
[0044] According to the present invention, preferably, step 3 includes the following steps: first, heat the carrier to 180-350°C, then spray it at a temperature of 250-300°C, and then dry it at 80-120°C for 1-3 hours.
[0045] According to the present invention, preferably, the activation treatment is carried out in a closed or activating atmosphere, wherein the activating atmosphere is nitrogen and / or helium.
[0046] The activation process includes the following steps:
[0047] (1) Increase the temperature from room temperature to 150℃ to 200℃ at a rate of 70 to 150℃ / h and hold for 5 to 30 minutes;
[0048] (2) Increase the temperature to 220-250℃ at a rate of 60-120℃ / h and hold for 5-30 minutes;
[0049] (3) Increase the temperature to 300-350℃ at a rate of 50-100℃ / h and hold for 10-60 minutes;
[0050] (4) Increase the temperature to 420-480℃ at a heating rate of 40-90℃ / h and maintain it for 5-10 hours;
[0051] (5) Cool to room temperature at a rate of 40-80℃ / h.
[0052] According to some embodiments of the present invention, the catalyst provided by the present invention is activated in a sealed container. The sealed container is a cylindrical or cubical activation furnace body, the upper part of which is sealed by a flange to isolate the internal space from the outside. An electric heating wire is wrapped around the outer wall of the furnace body, and insulation cloth or tiles are provided outside the electric heating wire. The heating temperature of the furnace body is controlled by an automated digital temperature controller. The furnace body has vents at the top and bottom; the lower vent serves as a gas inlet, and the upper vent serves as a gas outlet. The gas flow rate is controlled by a gas mass flow meter.
[0053] A third aspect of the present invention provides a method for the oxidation of benzene to maleic anhydride, wherein a benzene-containing gas mixture is contacted with the catalyst described above for improving the selectivity of the oxidation of benzene to maleic anhydride.
[0054] According to some embodiments of the present invention, in order to prevent the danger caused by excessively high benzene concentration, the concentration of benzene in the mixed gas is 40-55 g / Nm³. 3 .
[0055] According to some embodiments of the present invention, the volume hourly space velocity of the mixed gas is 1500-3000 h⁻¹. -1 .
[0056] According to some embodiments of the present invention, the volume hourly space velocity of the mixed gas is 2000-2500 h⁻¹. -1 .
[0057] According to some embodiments of the present invention, a molten salt bath is used to heat the reaction and remove the heat.
[0058] According to some embodiments of the present invention, the molten salt temperature used is 340-365°C.
[0059] According to some embodiments of the present invention, the reaction pressure is negative pressure, atmospheric pressure, and pressurized pressure.
[0060] According to some embodiments of the present invention, the reaction pressure is atmospheric pressure.
[0061] According to some embodiments of the present invention, the process uses a fixed-bed reactor immersed in molten salt, with heating and heat removal achieved through a molten salt bath. In the reaction of benzene oxidation to maleic anhydride, the temperature varies from top to bottom within the catalyst bed. The highest temperature value in this region is called the hot spot temperature of the catalyst, and the corresponding bed height is the hot spot location of the reaction bed. In this invention, thermocouples are used to measure the bed temperature. Benzene concentration refers to the number of grams of benzene contained in a unit volume of air; a higher value indicates a higher benzene content in the air.
[0062] The present invention will be further described below with reference to the embodiments, but the scope of the present invention is not limited to these embodiments.
[0063] Unless otherwise specified, the raw materials or components used in this invention can be obtained through commercial means or conventional methods. In the quantitative experiments in the following examples, three replicate experiments were set up, and the average value of the results was taken.
[0064] Example 1
[0065] Step 1: Take 500g of green silicon carbide carrier, 8g of MCM-41, and 8g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 2nm.
[0066] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0067] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0068] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst A.
[0069] Catalyst A was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0070] Example 2
[0071] Step 1: Take 500g of green silicon carbide carrier, 8g of MCM-41, and 8g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 50 and a pore size of 3nm.
[0072] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0073] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0074] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst B.
[0075] Catalyst B was loaded into the fixed-bed reactor and tested using a molten salt temperature of 350°C. The results are shown in Table 1.
[0076] Example 3
[0077] Step 1: Take 500g of green silicon carbide carrier, 8g of MCM-41, and 8g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 8nm.
[0078] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0079] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0080] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150℃ at a rate of 150℃ / h, and hold for 5 minutes. Then raise the temperature to 250℃ at a rate of 120℃ / h, and hold for 10 minutes. Next, raise the temperature to 350℃ at a rate of 100℃ / h, and hold for 20 minutes. Then raise the temperature to 450℃ at a rate of 90℃ / h, and hold at this temperature for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst C.
[0081] Catalyst C was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0082] Example 4
[0083] Step 1: Take 500g of green silicon carbide carrier, 22g of MCM-41, and 8g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 8nm.
[0084] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0085] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0086] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst D.
[0087] Catalyst D was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0088] Example 5
[0089] Step 1: Take 500g of green silicon carbide carrier, 8g of MCM-41, and 22g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 2nm.
[0090] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.5g of titanium nitrate and 1.5g of niobium nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0091] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0092] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst E.
[0093] Catalyst E was loaded into the fixed-bed reactor and tested using a molten salt temperature of 350°C. The results are shown in Table 1.
[0094] Example 6
[0095] Step 1: Take 500g of green silicon carbide carrier, 10g of MCM-41, and 12g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The MCM-41 molecular sieve has a silicon-to-aluminum ratio of 50 and a pore size of 6nm.
[0096] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.2g of titanium nitrate and 1.4g of potassium nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0097] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0098] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst F.
[0099] Catalyst F was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0100] Example 7
[0101] Step 1: Take 500g of green silicon carbide carrier, 10g of MCM-41, and 12g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 2nm.
[0102] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0103] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0104] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst G.
[0105] Catalyst G was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0106] Example 8
[0107] Step 1: Take 500g of green silicon carbide carrier, 10g of MCM-41, and 12g of MgO and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 2nm.
[0108] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0109] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0110] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst H.
[0111] Catalyst H was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0112] Example 9
[0113] Catalyst L was prepared using the same method as in Example 1, except that MCM-41 molecular sieve with a silicon-to-aluminum ratio of 2 was added. After being prepared as a support, it was sprayed, dried, and activated.
[0114] Catalyst L was loaded into the fixed-bed reactor and tested using a molten salt temperature of 350°C. The results are shown in Table 1.
[0115] Example 10
[0116] Catalyst M was prepared using the same method as in Example 1, except that MCM-41 molecular sieve with a silicon-to-aluminum ratio of 60 was added. After being prepared as a support, it was sprayed, dried, and activated.
[0117] Catalyst M was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0118] Example 11
[0119] Catalyst N was prepared using the same method as in Example 1, except that MCM-41 molecular sieve with a pore size of 1 nm was added. After being prepared as a support, it was sprayed, dried, and activated.
[0120] Catalyst N was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0121] Example 12
[0122] Catalyst O was prepared using the same method as in Example 1, except that MCM-41 molecular sieve with a pore size of 10 nm was added. After being prepared as a support, it was sprayed, dried, and activated.
[0123] Catalyst O was loaded into the fixed-bed reactor and tested using a molten salt temperature of 350°C. The results are shown in Table 1.
[0124] Example 13
[0125] Step 1: Take 500g of green silicon carbide carrier, 30g of MCM-41, and 8g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 4nm.
[0126] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0127] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0128] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst D.
[0129] Catalyst D was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0130] Example 14
[0131] Step 1: Take 500g of green silicon carbide carrier, 8g of MCM-41, and 30g of CeO2 and crush them in a pulverizer. Then mix them with methylcellulose and polypropylene, add water to form a slurry, and then put it into an extruder to process it into a ring shape. Then dry it at 120℃ for 12 hours. Finally, calcine the dried carrier at 800℃ to form a carrier suitable for spraying. The selected MCM-41 molecular sieve has a silicon-to-aluminum ratio of 5 and a pore size of 4nm.
[0132] Step 2: Dissolve 94g of oxalic acid in 500mL of water at room temperature, add 67.1g of ammonium metavanadate while stirring until the ammonium metavanadate dissolves and a homogeneous and stable solution is formed; dissolve 29.8g of ammonium molybdate in 40mL of water at 80℃ until it is evenly dissolved, and add this solution to the above ammonium metavanadate solution; while stirring, add 4.7g of trisodium phosphate, 1.5g of diammonium hydrogen phosphate, 1.1g of nickel nitrate, 1.0g of silver nitrate and 1.2g of copper nitrate in sequence, and mix to obtain the catalyst active mother liquor.
[0133] Step 3: Place 300g of the above ternary composite carrier into a rotating and heated stainless steel drum. The bottom of the carrier is equipped with a thermocouple sheath, and the internal thermocouple is connected to a temperature display instrument to show real-time temperature changes. When the carrier temperature reaches 250℃, spray the active mother liquor of the ink catalyst onto the carrier through a special nozzle at a spraying temperature of 250-300℃. After spraying, dry the catalyst precursor at 100℃ for 2 hours.
[0134] Step 4: Place 150g of the above catalyst precursor in an activation furnace, seal it, and raise the temperature from room temperature to 150°C at a rate of 150°C / h and hold for 5 minutes. Then raise the temperature to 250°C at a rate of 120°C / h and hold for 10 minutes. Next, raise the temperature to 350°C at a rate of 100°C / h and hold for 20 minutes. Then raise the temperature to 450°C at a rate of 90°C / h and hold for 5 hours. Then gradually lower the temperature to room temperature to obtain catalyst D.
[0135] Catalyst D was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0136] Comparative Example 1
[0137] Catalyst I was prepared using the same method as in Example 1, except that MCM-41 molecular sieve and CeO2 were not added. After being prepared into a support, it was sprayed, dried, and activated.
[0138] Catalyst I was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0139] Comparative Example 2
[0140] Catalyst J was prepared using the same method as in Example 1, except that MCM-41 molecular sieve was not added. After being prepared as a support, it was sprayed, dried, and activated.
[0141] Catalyst J was loaded into the fixed-bed reactor and tested using a molten salt temperature of 350°C. The results are shown in Table 1.
[0142] Comparative Example 3
[0143] Catalyst K was prepared using the same method as in Example 1, except that CeO2 was not added. After being prepared as a support, it was sprayed, dried, and activated.
[0144] Catalyst K was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0145] Comparative Example 4
[0146] Catalyst I was prepared using the same method as in Example 1, except that the MCM-41 molecular sieve was replaced with ZSM-5. After being prepared as a support, it was sprayed, dried, and activated.
[0147] Catalyst I was loaded into the fixed-bed reactor and tested using molten salt at a temperature of 350°C. The results are shown in Table 1.
[0148] Catalyst evaluation
[0149] The activated catalyst was loaded into a 120ml bubbling molten salt circulating reactor. The reactor was supported by an inert carrier at the bottom, with 120ml of catalyst in the middle and a certain height of inert carrier at the top. When the molten salt was heated to the required reaction temperature, air was introduced, and benzene was added simultaneously. After the benzene concentration reached the required operating concentration and stabilized for 1 hour, samples were taken for analysis. The evaluation results of each catalyst sample are shown in Table 1. The calculation methods for each index are as follows:
[0150] Benzene conversion rate (%) = (Amount of benzene at reactor inlet per unit time - Amount of benzene at reactor outlet per unit time) / Amount of benzene at reactor inlet per unit time × 100%
[0151] Maleic anhydride yield (%) = Benzene conversion × Maleic anhydride selectivity × 98 / 78 × 100%
[0152] Table 1. Results of activity evaluation in 120mL single tubes
[0153]
[0154] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
[0155] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A catalyst for improving the selectivity of benzene oxidation to maleic anhydride, characterized in that, It includes a carrier and an active component loaded on the carrier, wherein the carrier is a ternary composite carrier of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide; Specifically, based on the total weight of the carrier, the content of the weakly acidic molecular sieve material is 0.1-10 wt%, preferably 1-5 wt%, and the content of the weakly basic oxide is 0.1-10 wt%, preferably 1-5 wt%.
2. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 1, wherein, The weakly acidic molecular sieve material is selected from at least one of MCM-41 molecular sieve, MCM-48 and SBA-15, preferably MCM-41 molecular sieve, and more preferably, the silicon-aluminum ratio of MCM-41 molecular sieve is 5-50 and the pore size is 2-8 nm. The weakly basic oxide is selected from at least one of CeO2, MgO, ZnO and Ag2O.
3. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 1, wherein, The ternary composite carrier of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide is obtained by mixing, extruding, drying and calcining silicon carbide, weakly acidic molecular sieve material, weakly basic oxide, binder and solvent.
4. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 3, wherein, The ternary composite carrier of silicon carbide-weakly acidic molecular sieve material-weakly basic oxide has at least one shape selected from spherical, cylindrical, annular, clover-shaped and tetraclover-shaped.
5. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 3, wherein, The adhesive is selected from at least one of methylcellulose, polypropylene, starch, and dextrin; The solvent is water and / or ethanol.
6. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 1, wherein, Based on the total weight of the catalyst, the loading of the active component is 10-30 wt%, preferably 12-24 wt%.
7. The catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to claim 1, wherein, The active components include a main catalyst component and a co-catalyst component; The main catalyst components include vanadium, molybdenum, sodium, phosphorus, and nickel. The co-catalyst component includes alkali metal and / or transition metal compound elements, preferably selected from two of the compound elements of cesium, potassium, titanium, niobium, silver, and copper; The molar ratio of vanadium, molybdenum, sodium, phosphorus, nickel, and the co-catalyst component (calculated as metal element) is 1:(0.2-0.90):(0.001-0.2):(0.005-0.25):(0.0001-0.05):(0.0002-0.01), where the molar amounts of the co-catalyst component are calculated as V2O5, MoO3, Na2O, P2O5, NiO, and metal element, respectively.
8. A method for preparing the catalyst for improving the selectivity of benzene oxidation to maleic anhydride according to any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Take silicon carbide, weakly acidic molecular sieve material and alkaline oxide, crush them, mix them with binder and solvent, extrude them into shape, and then dry and calcine them to obtain the carrier. Step 2: Add the active substance to the reducing agent solution to obtain the active mother liquor; Step 3: Spray the active mother liquor onto the carrier to obtain the catalyst precursor; Step 4: Activate the catalyst precursor to obtain the catalyst for the oxidation of benzene to maleic anhydride.
9. The preparation method according to claim 8, wherein, In step 1, the drying conditions include: a temperature of 100-140℃ and a time of 8-20 hours; The roasting conditions include a temperature of 800-1200℃ and a time of 2-10 hours.
10. The preparation method according to claim 8, wherein, In step 2, the reducing agent is selected from at least one of oxalic acid, ammonium oxalate and urea.
11. The preparation method according to claim 8, wherein, The compounds containing active substances include compounds containing main catalyst components and compounds containing co-catalyst components; The compound containing the main catalyst component includes vanadium compounds, molybdenum compounds, sodium compounds, phosphorus compounds, and nickel compounds; the vanadium compound is preferably selected from at least one of ammonium metavanadate, vanadium pentoxide, and sodium vanadate; the molybdenum compound is preferably selected from at least one of ammonium molybdate, molybdenum trioxide, and calcium molybdate; the sodium compound is preferably selected from sodium dihydrogen phosphate and / or trisodium phosphate; the phosphorus compound is selected from at least one of ammonium dihydrogen phosphate, 85%-115% phosphoric acid, and phosphorus pentoxide; and the nickel compound is selected from at least one of nickel nitrate, nickel sulfate, nickel chloride, and nickel oxide. The compound containing the co-catalyst component includes alkali metal and / or transition metal compounds, preferably selected from two compounds of cesium, potassium, titanium, niobium, silver, and copper; Preferably, the molar ratio of the vanadium compound (calculated as V2O5), the molybdenum compound (calculated as MoO3), the sodium compound (calculated as Na2O), the phosphorus compound (calculated as P2O5), the nickel compound (calculated as NiO), and the compound containing the co-catalyst component (calculated as metal element) is 1:(0.2-0.90):(0.001-0.2):(0.005-0.25):(0.0001-0.05):(0.0002-0.010).
12. The preparation method according to claim 8, wherein, Step 3 includes the following steps: first, heat the carrier to 180-350℃, then spray it at a temperature of 250-300℃, and then dry it at 80-120℃ for 1-3 hours.
13. The preparation method according to claim 8, wherein, In step 4, the activation process is carried out in a closed or activating atmosphere, wherein the activating atmosphere is nitrogen and / or helium. The activation process includes the following steps: (1) Increase the temperature from room temperature to 150℃ to 200℃ at a rate of 70 to 150℃ / h and hold for 5 to 30 minutes; (2) Increase the temperature to 220-250℃ at a rate of 60-120℃ / h and hold for 5-30 minutes; (3) Increase the temperature to 300-350℃ at a rate of 50-100℃ / h and hold for 10-60 minutes; (4) Increase the temperature to 420-480℃ at a heating rate of 40-90℃ / h and maintain it for 5-10 hours; (5) Cool to room temperature at a rate of 40-80℃ / h.
14. A method for producing maleic anhydride by benzene oxidation, characterized in that, The benzene-containing gas mixture is contacted with the catalyst described in any one of claims 1-7 for improving the selectivity of benzene oxidation to maleic anhydride.
15. The method for producing maleic anhydride by benzene oxidation according to claim 14, wherein, The benzene concentration in the benzene-containing gas mixture is 40-55 g / Nm³. 3 And / or, the volume hourly space velocity of the benzene-containing gas mixture is 1500-3000 h⁻¹. -1 Preferably 2000-2500h -1 And / or, the temperature of the contact is 340-365°C.
